TRANSLATION SHIFTS IN THE TEXTS OF DIORAMA DISPLAY AT THE NATIONAL HISTORY MUSEUM IN INDONESIAN NATIONAL MONUMENT (MONAS) - Deuis Sugaryamah; Gifa Rokhimah Anggreyani (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
This paper presents the result of a study related to the translation shifts procedure in the translation of Indonesian into English texts of the diorama display at the History Museum in National Monument Jakarta. The 51 (fifty one) pair of texts available in the displays are used as the main data. The data were collected by using documentation, and by taking pictures of the entire texts in the label of the dioramas. Using the Catford’s theory of translations shift, the four types of category shifts revealed in the texts are structure shifts, class shifts, unit shifts, and intra-system shifts. Meanwhile, the data presenting level shift was found unavailable in the texts.